Une école publique dans une maison : transition franche ou rupture douce ? - Jean-François Manil (Éducation et Socialisation)
The House of the Children of Buzet (B.-CWB.) is a public primary school organized in a village house. The pedagogical dynamics which reign there relies on the principles of the New Education. This article attempts to describe the interactions between architecture, school organizations and pupils feelings